World Images and The Time-Space Notions: From An Epistemological Point of View - Scribano, Adrián Oscar (2014)
This paper propose to show the relevance of a reconsideration of the time-space notions, in order to make possible an epistemological analysis of the world images as an ontological component of theories. The argumentative strategy is: (a) the role of notions of time/space in Bourdieu’s theory as a component of his world image is summarized, and (b) is synthesized in which direction to reconsider the notions of time/space is important from an epistemological point of view for the social sciences and human existence.